TELAAH VISUM ET REPERTUM SEBAGAI FAKTOR PENENTU DALAM PEMBUKTIAN PADA PUTUSAN NOMOR 208/PID.B/2022/PN BDG - Dimas Bagus Anggoro Bangun; Itok Dwi Kurniawan (Verstek, 2023)
This study aims to determine how the Magistrate Judges' legal considerations are based on Visum et Repertum and how Visum et Repertum is a determining factor in proving theft charges with violence resulting in death in death Decision Number 208/Pid.B/2022/PN.Bdg. This is normative legal research that is prescriptive and applied to case studies. The technique of collecting primary and secondary legal materials used for this research is a documental study and literature materials. Regarding the results of the research and discussion, it can be seen that the considerations of the Magistrate Judges in Decision Number 208/Pid.B/2022/PN.Bdg have included juridical and non-juridical aspects. Magistrate Judges require the opinion of a doctor as outlined in the Visum et Repertum, bearing in mind that the judge as a case breaker is not equipped with knowledge related to forensic medicine, so he must pay attention to Visum et Repertum as one piece of evidence that is adapted to other evidence. In addition, Visum et Repertum is a determining factor in proving the indictment of Decision 208/Pid.B/2022/PN.Bdg because it has strength in evidence, namely through matching Visum et Repertum with witness statements, which results are used as conclusions for judges who can be used as a consideration in determining whether a crime has occurred or not and determining the guilt of the defendant at trial.